IDENTIFIKASI FAKTOR RISIKO KEJADIAN PENYAKIT JANTUNG KORONER DI RUMAH SAKIT UMUM HAJI SURABAYA - Retno Sumara (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:   This study aims to to determine the risk factors for coronary heart diseaseMethods:   The study used a descriptive research design with a population of all coronary heart disease patients in the Cardiac Inpatient Room at the Haji General Hospital in Surabaya. The population is 108 RM of CHD patients using Simple Random Sampling of 85  patient data with CHD. Data collection was taken from Medical Records by taking data: Age, Gender, Education, Occupation, Height, Weight, History of Hypertension, History of Diabetes Mellitus.Results:   The results showed Coronary Heart Disease based on age Demographic Factors, most were aged 48-55 years, 22 patient data (25.9%), based on gender, most were male, 43 patient data (50.6%) and female, 42 patient data (49 ,4 %). Based on the history of coronary heart disease, the majority did not have a history of CHD 54.10%, had a history of hypertension 74.10%, had a history of diabetes mellitus 61.20% and obesity 63.50%.Conclusion:  Coronary heart disease is caused by atherosclerosis which is caused by the accumulation of lipids in the walls of the coronary arteries. Lipid deposits can form a thrombus that can block blood flow.